2021
DOI: 10.1155/2021/8868543
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Diarrhoea among Children Under Five Years in Southwest Nigeria

Abstract: Diarrhoea is the passage of three or more loose or liquid stools per day or more frequent passage than is normal for an individual. Diarrhoea alters the microbiome, thus the immune system, and is a significant cause of morbidity and mortality in young children. This study evaluated the association between the risk factors and diarrhoea prevalence among children under five years in Lagos and Ogun States, located in Southwest Nigeria. Participants included 280 women aged 15–49 years and children aged 0–59 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Our study also showed that in children, male sex, with poorly educated mothers, and younger age were associated with a higher risk of diarrhoea. Previous studies showed similar results with mothers' education and recommend that female education should be encouraged to enhance the survival of neonates and infants (40) . Higher rates of diarrhoea in younger children from 6 to 35 months than in older children are likely due to the weaning occurring at 6 months in most children.…”
Section: Discussionsupporting
confidence: 58%
“…Our study also showed that in children, male sex, with poorly educated mothers, and younger age were associated with a higher risk of diarrhoea. Previous studies showed similar results with mothers' education and recommend that female education should be encouraged to enhance the survival of neonates and infants (40) . Higher rates of diarrhoea in younger children from 6 to 35 months than in older children are likely due to the weaning occurring at 6 months in most children.…”
Section: Discussionsupporting
confidence: 58%
“…The selection of the variables was influenced by their association with childhood diarrhea in several previous studies in Nigeria. 31 - 33 …”
Section: Methodsmentioning
confidence: 99%
“…Numerous sociodemographic, environmental, and behavioral factors contribute to the prevalence of diarrheal disease among children under the age of five [ 7 , 8 ]. Key sociodemographic factors encompass the child’s age, place of residence, maternal education, and household economic status [ 7 - 10 ].…”
Section: Introductionmentioning
confidence: 99%